(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines critical success factors for implementing Agricultural Technology (AgriTech) solutions in rural African Small and Medium Enterprises (SMEs), focusing on comparative case studies from Zimbabwe, Kenya, Nigeria, Ghana, and Rwanda. The research adopts a comprehensive desk review methodology, analyzing recent literature, policy documents, and implementation reports from 2020-2025. Key findings reveal that successful AgriTech implementation depends on five primary factors: robust stakeholder involvement encompassing government, private sector, academia, and farmer organisations; comprehensive ICT infrastructure development including broadband connectivity and digital literacy programs; sustained capacity building initiatives targeting technical skills and agricultural knowledge; deliberate gender inclusion strategies addressing women farmers' specific needs; and innovative public-private partnership models facilitating resource mobilisation and risk sharing. The study identifies significant barriers including the digital divide affecting 61% of rural African populations, funding constraints limiting technology adoption, and skills gaps impeding effective utilisation. Comparative analysis demonstrates that countries with integrated national digital agriculture strategies, such as Rwanda's Smart Agriculture program and Kenya's DigiFarm platform, achieve higher implementation success rates. The research contributes to understanding how contextual factors influence AgriTech adoption patterns across different African economies. Results indicate that successful implementations require minimum 3:1 return on investment demonstration, localised content development, and phygital service delivery combining digital and physical channels. The study concludes that sustainable AgriTech implementation necessitates holistic approaches addressing technological, social, economic, and institutional dimensions simultaneously. Key policy takeaways include prioritising gender-inclusive public-private partnership models with demonstrated 3:1 ROI benchmarks and establishing national broadband rollouts achieving minimum 85% rural coverage to ensure equitable technology access across diverse agricultural contexts.